Relevansi Mukjizat Al-Quran Dalam Menjawab Tantangan Etika Kontemporer - Ghinayatus Salwa; Hanif Akbar; 'Aisyina Sailan Ilal 'Izza Mursyid; Umar Al-Faruq (Ta'limDiniyah: Jurnal Pendidikan Agama Islam (Journal of Islamic Education Studies), 2023)
Abstract This study aims to explore the relevance of the miracles of the Al-Quran in responding to the ethical challenges faced in the context of contemporary society. Through a literature study approach, this article analyzes relevant literary sources to explore a deeper understanding of the potential miracles of the Al-Quran in providing relevant moral foundations and ethical principles. This study finds that the miracles of the Al-Quran have universal ethical values and are relevant to contemporary ethical challenges. The Koran emphasizes the importance of moral integrity, justice, compassion, social responsibility, gender justice, and respect for the environment. The miracles of the Al-Quran also provide guidance in overcoming complex ethical dilemmas, including issues of bioethics, technology, social justice, and ecology. This study concludes that the miracles of the Al-Quran have significant potential in providing a moral foundation and ethical principles that are relevant to facing contemporary ethical challenges. Understanding and applying the ethical values contained in the miracles of the Al-Quran can enrich global ethical discourse and create a more just, sustainable and dignified society in the contemporary era.